Whole-abdomen, single-dose consolidation radiotherapy in patients with pathologically confirmed complete remission of advanced ovarian epithelial carcinoma: a long-term survival analysis. Issue 5 (1st August 2004) - Debby, A.; Levy, T.; Hayat, H.; Brenner, Y.; Glezerman, M.; Menczer, J.
Abstract : The value of consolidation therapy in advanced epithelial ovarian carcinoma patients is controversial. The aim of the present study was to assess the long-term survival of patients with a pathologically confirmed complete remission who had consolidation by single-dose, whole-abdominopelvic radiotherapy. Of 96 histologically confirmed stage II–IV epithelial ovarian carcinoma patients who underwent cytoreductive surgery followed by high-dose, platin-based chemotherapy, 57 were in complete clinical remission at the end of therapy and 50 underwent a second-look laparotomy. The study group comprises 32 consecutive patients who had no pathological evidence of disease and who received 800 cGy single-dose, whole-abdominal radiotherapy by an 8 MEV linear accelerator in a single fraction. The absolute 5-year survival and the actuarial 10-year survival were 78.7 and 63.3%, respectively. The survival was significantly better in patients who had ≤2 cm residual disease at the completion of the original operation. No severe postradiation complications were encountered. Mild complications were seen in three (9.4%) patients. Our data indicate a favorable long-term survival of patients with a negative second-look laparotomy who had consolidation with single-dose, whole-abdominal radiotherapy. These results seem to suggest that a collaborative, prospective, randomized multiarm study is indicated to solve the controversial issue of consolidation therapy.